Towards model-based approaches for musical instruments making: validation of the model of a Spanish guitar soundboard and characterization features proposal. (15th January 2021) - Viala, Romain; Pérez, Marco A.; Placet, Vincent; Manjón, Antonio; Foltête, Emmanuel; Cogan, Scott
Highlights: Model validation of musical instrument part even in presence of strong uncertainties. Fuzzy-FRF method illustrated to musical acoustics domain. Screening analysis of material and climatic parameters on guitar soundboard dynamics. Similar impact of E L ρ, E R ρ, G LR ρ and RH on soundboard dynamics in free conditions. Predominance of E L ρ, followed by E R ρ, G LR ρ on eigenmode shapes. Abstract: Nowadays, the virtual prototyping method is widely used for industrial applications and can lead to a powerful tool for musical instruments making and conservation. Nevertheless, physics-based models of musical instruments are barely developed for this purpose and the confrontation between model predictions and experiments have been the focus of very few researches. The objective of this paper is to highlight the predictive capability of physics-based models in vibratory domain, even in presence of variable by nature material and climatic conditions. To this end, a finite element model of the soundboard of a Spanish guitar is developed for model validation purposes. The simulated modal bases are compared with experimental ones from a previous study. Screening and stochastic analyses are performed to rank which are, among material and climatic parameters, the most influential ones on the dynamics of guitar soundboard. Moreover, uncertainties are taken into account to evaluate the dispersion of the response for a given design, and simulations are validated facing experimental data. It is shown that specific elastic parameters of the wood (in longitudinal and radial directions and longitudinal-radial plane) of the top plate are mainly influential with regard to the dynamics of the soundboard, and the relative humidity changes have a non negligible impact. Moreover, test-model correlations have shown that a nominal model with average material parameters is able to predict the vibratory behaviour of a real braced soundboard with an average error on the first eight eigenfrequencies lower than 4%. In addition, when uncertainties are taken into account, the model is able to predict every experimental data. Finally, dynamic features like CFDAC and Fuzzy-FRF are proposed in an innovative way in this application domain.